Doubling Dublin: Mimetic and Anti-Mimetic Use of Urban Space in Flann O’Brien’s At Swim-Two-Birds - Szot, Barbara (Hungarian Journal of English and American Studies, 2020)
The article examines the use of references to the topography of Dublin in mimetic and anti-mimetic sections of Flann O’Brien’s At Swim-Two-Birds (1939). It studies the three different layers of fiction that have been defined on the basis of their ontological status within the narrative. The article argues that references to actual Dublin locations serve as a means of building and then breaking the mimetic framework of the seemingly realistic descriptions that belong to the first two layers (“reality” and “fiction” within the novel). The strikingly anti-mimetic Western novel sections (“fiction within fiction”), which lack any credibility in their depiction of Dublin, can be seen as a radical rewriting of the urban space that does in fact have the actual city’s character at its core. O’Brien thus unsettles the conventions (and the readers’ expectations) and explores the possibilities of representing elements of the real world in fiction.